ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI JAGUNG DI KECAMATAN JUNREJO KOTA BATU - Azzuhri Tri Ahara; Arif Hoetoro (Jurnal Ilmiah Mahasiswa FEB, 2015)
The aimed of this study to analyze the factors affecting revenue toward farmers in the Junrejo District Batu. The dependent variable in this research is the revenue received by Farmers in a farming cycle. Meanwhile, the land area, the amount of capital, the amount of the crop, age of the farmer and the amount of labor is an independent variable. The selected sample is 3 villages with the highest number of households cultivate maize crop in the Junrejo District such as Junrejo Village, Tlekung Village, and Dadaprejo Village. OLS regression analysis results showed that at the 95 percent confidence level, land area, the amount of capital, the amount of the crop, and the number of workers has a significant impact on farmers' revenue. While the age of the farmer has no significant effect on farmers' revenue. Keywords: Revenue, Farmers, Land Area, Total Capital, Total Yield, Age Farmers, Total Labor.